Achieving High‐Performance Metal Phosphide Anode for Potassium Ion Batteries via Concentrated Electrolyte Chemistry. Issue 6 (31st December 2020) - Yang, Fuhua; Hao, Junnan; Long, Jun; Liu, Sailin; Zheng, Tian; Lie, Wilford; Chen, Jun; Guo, Zaiping
Abstract: Metal phosphides are regarded as promising anode candidates for high‐energy‐density potassium‐ion batteries (PIBs) due to their high theoretical capacity and relatively low operation voltage. The failure mechanism of the metal phosphides originates from the large volume variation during cycling, which leads to fast capacity degradation. Herein, concentrated electrolyte is used to achieve impressive cycling stability for K‐metal and K‐ion batteries over their more dilute counterparts, mainly benefiting from the anion‐derived robust and uniform solid–electrolyte interphase layer, which is helpful in maintaining the electrode integrity, avoiding excessive side reactions, and suppressing electrolyte decomposition. Further investigations also reveal the synergistic advantages of the superior chemical compatibility of concentrated electrolyte to potassium metal, as well as its remarkable electrochemical stability and enhanced safety compared to conventional dilute electrolytes. This work provides a feasible strategy to mitigate the degradation of metal phosphides to build high‐energy‐density PIBs. Abstract : Concentrated electrolyte is used to achieve impressive cycling stability for K‐metal and K‐ion batteries compared to more dilute counterparts, mainly benefiting from the anion‐derived robust and uniform solid–electrolyte interphase layer, which is helpful in maintaining the electrode integrity, avoiding excessive side reactions, and suppressing electrolyte decomposition.